2012
DOI: 10.1016/j.ijantimicag.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of miltefosine treatment in Leishmania amazonensis-infected BALB/c mice

Abstract: Leishmaniasis is one of the most serious worldwide diseases caused by protozoan parasites of the Leishmania genus, affecting millions of people around the world. All currently available treatments present severe toxic side effects, require long-term compliance, cause serious side effects and are uncomfortable for patients. Leishmania amazonensis, a species endemic to Brazil, causes severe localised or diffuse skin lesions in humans. Owing to the unsatisfactory nature of the currently available chemotherapies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…The World Health Organization recommends 2.5 mg/kg/day MF for 28 days for the treatment of CL or VL in humans. This scheme is not effective for obtaining complete cure in L. amazonensis infected BALB/c mice [36]. Previous studies in our laboratory indicated that MF was effective in the treatment of L. amazonensis infections in BALB/c mice if used at 13 mg/kg/day for 15 days by the oral route (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…The World Health Organization recommends 2.5 mg/kg/day MF for 28 days for the treatment of CL or VL in humans. This scheme is not effective for obtaining complete cure in L. amazonensis infected BALB/c mice [36]. Previous studies in our laboratory indicated that MF was effective in the treatment of L. amazonensis infections in BALB/c mice if used at 13 mg/kg/day for 15 days by the oral route (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…Forty BALB/c mice (four weeks old; weight ~ 25 g) were inoculated at the base of the tail with 2 × 10 7 promastigote forms of L. amazonensis in stationary phase of growth (final volume 25 µL) as described in previous published works [ 9 , 46 , 47 , 48 , 49 ]. Five healthy control group was injected only with physiological solution.…”
Section: Methodsmentioning
confidence: 99%
“…All the treatments were given with a single daily dose of 20 µL, under intralesional route. The highest doses of 50.0 mg/kg from Glu was selected based on previously published works [ 47 , 50 , 51 ]. Treatment outcome was determined by skin parasitism that was analyzed one week after the end of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of any suitable vaccine against visceral leishmaniasis (VL), chemotherapy is the only option for control of the disease. Although the treatment for leishmaniasis was introduced in the early 20th century, parenteral administration of pentavalent antimony compounds (meglumine antimoniate and sodium stibogluconate) remains the first‐choice treatment for all forms of leishmaniasis . In the case of antimonial resistance, the second‐choice treatment includes amphotericin B (deoxycholate or liposomal formulation) .…”
Section: Introductionmentioning
confidence: 99%
“…Although the treatment for leishmaniasis was introduced in the early 20th century, parenteral administration of pentavalent antimony compounds (meglumine antimoniate and sodium stibogluconate) remains the first‐choice treatment for all forms of leishmaniasis . In the case of antimonial resistance, the second‐choice treatment includes amphotericin B (deoxycholate or liposomal formulation) . However, each of these therapies has important limitations, such as long‐term parenteral administration, toxic side effects, high cost in endemic countries and an increase in number of resistance cases .…”
Section: Introductionmentioning
confidence: 99%